2023
DOI: 10.1158/0008-5472.c.6511711.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Extracellular Vesicles from Cancer-Associated Fibroblasts Containing Annexin A6 Induces FAK-YAP Activation by Stabilizing β1 Integrin, Enhancing Drug Resistance

Abstract: <div>Abstract<p>Extracellular vesicles (EV) from cancer-associated fibroblasts (CAF) are composed of diverse payloads. Although CAFs impact the aggressive characteristics of gastric cancer cells, the contribution of CAF-EV to gastric cancer progression has not been elucidated. Here, we investigated the molecular mechanism of the changes in gastric cancer characteristics induced by CAF-EV. CAF abundance in gastric cancer tissues was associated with poor prognosis of patients with gastric cancer rece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, how to change the biological function by ITGB1 needs further study. Consistently, the integrin family was implicated as an important inducer of tumorigenesis, and it was significantly implicated in cancer metastasis (81), drug resistance (82), and immune evasion (83), and it was clear that ITGB1 was one of the most important integrin family members. In terms of metabolism, current studies have shown that integrin activity can regulate insulin sensitivity in adipocytes and thereby systemic metabolism (84).…”
Section: B Amentioning
confidence: 90%
“…However, how to change the biological function by ITGB1 needs further study. Consistently, the integrin family was implicated as an important inducer of tumorigenesis, and it was significantly implicated in cancer metastasis (81), drug resistance (82), and immune evasion (83), and it was clear that ITGB1 was one of the most important integrin family members. In terms of metabolism, current studies have shown that integrin activity can regulate insulin sensitivity in adipocytes and thereby systemic metabolism (84).…”
Section: B Amentioning
confidence: 90%